2019
DOI: 10.1242/jcs.228478
|View full text |Cite
|
Sign up to set email alerts
|

Dkk1 exacerbates doxorubicin-induced cardiotoxicity by inhibiting the Wnt/β-catenin signaling pathway

Abstract: The cancer clinical therapy of doxorubicin (Dox) treatment is limited by its life-threatening cardiotoxic effects. Dickkopf-1 (Dkk1), the founding and best-studied member of the Dkk family, functions as an antagonist of canonical Wnt/β-catenin. Dkk1 is considered to play a broad role in a variety of biological processes, but its effects on Dox-induced cardiomyopathy are poorly understood. Here, we found that the level of Dkk1 was significantly increased in Dox-treated groups, and this increase exacerbated Dox-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…Wnt/β‐catenin signalling has been reported to be an inducer for cardiac hypertrophy, and inactivation of this signalling ameliorated hypertensive heart disease . It is reported Dkk1 inhibits Wnt signalling to regulate early myocardial proliferation Dkk1 exacerbates doxorubicin‐induced cardiotoxicity by inhibiting the Wnt/β‐catenin signalling pathway . It is indicating a significant role of DKK1 in the heart diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Wnt/β‐catenin signalling has been reported to be an inducer for cardiac hypertrophy, and inactivation of this signalling ameliorated hypertensive heart disease . It is reported Dkk1 inhibits Wnt signalling to regulate early myocardial proliferation Dkk1 exacerbates doxorubicin‐induced cardiotoxicity by inhibiting the Wnt/β‐catenin signalling pathway . It is indicating a significant role of DKK1 in the heart diseases.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to molecular mechanisms, our results indicate that the effects of TGFβ1 on bone mineralization may involve DKK1, which is a secreted protein originally located within the endoplasmic reticulum (ER) in the cytoplasm. Several studies have found that ER stress induces DKK1 secretion, eventually leading to cell apoptosis [ 35 , 36 , 37 ]. Osteoblasts can either transform when they are embedded in bone as osteocytes or undergo apoptosis for bone mineralization at the end phase of bone formation [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lin28a overexpression significantly decreased RhoA/ROCK signaling to alleviate mitochondria cristae destruction and promote heart function in diabetic mice (Sun et al, 2016). Additionally, Dkk1 adenovirus is transduced by intramyocardial injection, and Dkk1 overexpression aggravates Dox-induced CM apoptosis via the mitochondrial damage pathway (Liang et al, 2019). AAV serotype 9 (AAV-9) Plscr4, lncRNA-Plscr4 overexpression attenuates the hypertrophic response in hyperpressure-loaded CMs (Liu et al, 2020).…”
Section: Gene Editing For Genetic Disordermentioning
confidence: 99%